Economic software - information support of product cost management - A. Látečková; E. Škorecová (Agricultural Economics (AGRICECON), 2003)
Adequate product cost economic management is not possible at present without economic software application. Based on the analysis of the current state of enterprise information systems in agriculture, we define basic methods of automatic processing of economic trials and this on the enterprise management level and in-plant level. For product cost management enhancement, we recommend managerial information system application, which introduces extension of enterprise information system and allow real time cost analyse with multidimensional disintegration. We also introduce requirements that economic software suitable for information management needs should ensure.